The Effect of Identity Card Services on Community Satisfaction at The South Birobuli Village Office South Palu District - Rukhayati, Rukhayati; Mutiara, Anna Hernanda (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
Services carried out and implemented by the South Birobuli Urban Village Office, South Palu sub-district, as an effort to meet the community's needs with the function of making identity cards, family cards, and domicile letters to carry out regional government affairs. Meeting the community's needs is not expecting profit but on community satisfaction, in this case, the joy of the service user community. In achieving this goal, government agencies are more focused on serving the best. The purpose of this study was to determine and analyze the effect of tangible, reliable, responsiveness, assurance, and attention (empathy) simultaneously and partially on community satisfaction at the South Birobuli Village Office, Palu District. South. By using multiple linear regression analysis tools, research results and hypothesis testing are obtained that tangible (physical evidence), reliability, responsiveness, assurance, and empathy (attention) simultaneously or partially have a significant effect on community satisfaction—south birobuli at the South Birobuli Urban Village Office, South Palu District.